The Power of Pacta Sunt Servanda Principle in Arbitration Agreement - Mosgan Situmorang (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2021)
Pacta sunt servanda is a legal principle that applies universally. With this principle, everyone is expected to carry out an agreement made with other parties voluntarily. To enforce the principle by the court in case of dispute in the implementation of the agreement, it requires conditions that must be met. In the context of an arbitration agreement, it must also meet specific rules stipulated in the Arbitration Law. In practice, there is still disobedience to this principle where the parties who have been bound by an arbitration agreement are still taking the litigation in solving their case. In this research, the problems examined are how the principle of pacta sunt servanda is regulated in the arbitration law and how strong this principle is applied. The method used in this research is normative juridical. Based on the research, it is concluded that the implementation of the pacta sunt servanda principle is regulated in several articles of the Arbitration Law. The pacta sunt servanda principle is not valid absolutely because it is deviated by other laws or legal principles. It is recommended that parties in an agreement shall understand the choice of dispute settlement well including the consequences of such choice.